Increased Catalase Activity and Maintenance of Photosystem II Distinguishes High-Yield Mutants From Low-Yield Mutants of Rice var. Nagina22 Under Low-Phosphorus Stress - Poli, Yugandhar; Nallamothu, Veronica; Balakrishnan, Divya; Ramesh, Palakurthi; Desiraju, Subrahmanyam; Mangrauthia, Satendra Kumar; Voleti, Sitapathi Rao; Neelamraju, Sarla (Frontiers in Plant Science, 2018)
An upland rice variety, Nagina22 (N22) and its 137 EMS-induced mutants along with sensitive variety Jaya were screened both in low P (Olsen P 1.8) and normal field (Olsen P 24) during dry season. Based on grain yield/ plant in low P field, 27 gain of function (high yield hy) and 9 loss of function (low yield ly) mutants were selected by comparing with N22 for physiological and genotyping studies. In low P field, hy mutants showed higher root P, leaf P, grain P and total P concentration than ly mutants at harvest. In low P condition, Fv/Fm and qN were 24% higher in hy mutants than ly mutants. In comparison to ly mutants, SOD activity in the root and leaf of hy mutants in low P field was 9% and 41% higher at vegetative stage, but 51% and 14% lower at reproductive stage. CAT activity in the root and leaf of hy mutants in low P field was 35% higher at vegetative stage, 15% and 17% higher at reproductive stage than in ly mutants. Similarly, hy mutants showed 20% and 80% higher POD activity at vegetative stage but 14% and 16% lower activity at reproductive stage in the root and leaf in low P field. Marker trait association analysis using 48 SSR markers and 10 markers for Pup1 gene showed that RM3648 and RM451 in chromosome 4 were significantly associated with grain yield, tiller number, SOD and POD activity in both root and leaf only in low P condition. Likewise, RM3334 and RM6300 in chromosome 5 were associated with CAT activity in leaf in low P condition. It is noteworthy that grain yield was positively and significantly correlated with CAT activity in root and shoot, Fv/Fm and qN in low P condition, and with shoot P concentration and qN in normal condition. Also, CAT activity in shoot was positively and significantly correlated with tiller number in both low P and normal conditions. Thus, chromosomal regions and physiological traits that have a role in imparting tolerance to low phosphorus in the field were identified.